2021
DOI: 10.3390/antiox10111684
|View full text |Cite
|
Sign up to set email alerts
|

Extracts of Waste from Poplar Wood Processing Alleviate Experimental Dextran Sulfate-Induced Colitis by Ameliorating Oxidative Stress, Inhibiting the Th1/Th17 Response and Inducing Apoptosis in Inflammatory Lymphocytes

Abstract: As a fast-growing tree, poplar is widely planted and typically used for wood processing in China. During poplar wood processing, a large amount of poplar sawdust (PS) and poplar leaves (PL) are produced and abandoned. To make full use of poplar resources and clarify the use of poplar as a feed additive, the active ingredients in PS and PL were extracted and isolated, and the anti-inflammatory effects of the extracts on mice with dextran sulfate sodium (DSS)-induced colitis were investigated. In vitro anti-infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…A number of evidences indicated that alcohol exposure led to increased lipopolysaccharides (LPS), which provides the first signal for inflammasome activation [ 17 ]. LPS and ROS then induce the production and release of pro-inflammatory cytokines TNF-α and IL-6 [ 18 ]. IL-1β is critical to ALD pathogenesis, as it amplifies pro-inflammatory cytokine production, sensitizes hepatocytes to death signals and induces hepatic steatosis by upregulating FASN [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of evidences indicated that alcohol exposure led to increased lipopolysaccharides (LPS), which provides the first signal for inflammasome activation [ 17 ]. LPS and ROS then induce the production and release of pro-inflammatory cytokines TNF-α and IL-6 [ 18 ]. IL-1β is critical to ALD pathogenesis, as it amplifies pro-inflammatory cytokine production, sensitizes hepatocytes to death signals and induces hepatic steatosis by upregulating FASN [ 19 ].…”
Section: Introductionmentioning
confidence: 99%